Determinants of Teachers' Technology Adoption in Yogyakarta Classrooms: Exploring the Role of Skills, Infrastructure, and Leadership Policies - Martina Sunartiningsih; Udik Budi Wibowo; Muh. Saidil Ikhwan (STAI Hubbulwathan Duri, 2025)
This study explores the factors influencing teachers' ability to integrate technology in classroom instruction, specifically within schools in Yogyakarta. As digital tools become integral to education, understanding these factors is essential to supporting effective technology adoption in teaching practices. A qualitative case study approach was employed, involving six teachers from three schools in Yogyakarta selected through purposive sampling. Data were gathered using semi-structured interviews and document analysis. The research process included participant selection, instrument validation, and thematic data analysis to identify patterns related to technology integration challenges and strategies. The findings reveal three primary factors affecting technology use among teachers: (1) teachers’ knowledge and digital skills, (2) availability of infrastructure and technical support, and (3) school principals' policies and leadership. These elements significantly influenced teachers' confidence and motivation to utilize technology effectively in their teaching. The results underscore the need for continuous professional development, equitable access to technological infrastructure, and strong, supportive leadership to promote a tech-enabled educational environment. These factors collectively shape teachers’ readiness and willingness to adopt digital tools. To foster more effective technology integration in classrooms, stakeholders must prioritize teacher training, improve infrastructure, and encourage proactive leadership. Future research could expand on this study by comparing urban and rural school settings to examine contextual differences in teachers’ perceptions and experiences with educational technology.